Optimal visuo-vestibular integration for self-motion perception in patients with unilateral vestibular loss. (March 2018) - Kaliuzhna, Mariia; Gale, Steven; Prsa, Mario; Maire, Raphael; Blanke, Olaf
Abstract: Unilateral vestibular loss (UVL) is accompanied by deficits in processing of visual and vestibular self-motion cues. The present study examined whether multisensory integration of these two types of information is, nevertheless, intact in such patients. Patients were seated on a rotating platform with a screen simulating 3D rotation in front of them and asked to judge the relative magnitude of two successive rotations in the yaw plane in three conditions: vestibular stimulation, visual stimulation and bimodal stimulation (congruent stimuli from both modalities together). Similar to findings in healthy controls, UVL patients exhibited optimal multisensory integration during both ipsi- and contralesional rotations. The benefit of multisensory integration was more pronounced on the ipsilesional side. These results show that visuo-vestibular integration for passive self-motion is automatic and suggests that it functions without additional cognitive mechanisms, unlike more complex multisensory tasks such as postural control and spatial navigation, previously shown to be impaired in UVL patients. Highlights: Patients with unilateral vestibular loss integrate visuo-vestibular cues. This integration is optimal. Optimality is maintained for contra- and ipsilesional rotations.